J-Pine Enterprise / Mohamad Ramadhan Abdullah...[et.al] - Abdullah, Mohamad Ramadhan; Ku Ismail, Ku Izzat Hafiz; Ahmad Nasri, Nor Shahrina Nabilah; Abu Bakar, Azlina; Ab Azizi, Yuhanis Syuhada (Faculty of Plantation and Agrotechnology, 2016)
Carbohypaper Pineapple Leaf is actually paper which is consist of waste product from pineapple leaf. By doing some of observation and studies, we have decided to choose and set up our company at Johor Darul Takzim. Our main office is located at No. 44 Jalan Temenggong Ahmad, 84000 Muar, Johor Darul Takzim near to Sekolah Kebangsaan Parit Pinang Seribu .Actually, there are sort of reason, why we are choosing this kind of product and business. It is because, our General Manager, Mohamad Ramadhan Bin Abdullah, have basic information, knowledge and experience about this product. Furthermore, the production of Carbohypaper Pineapple Leaf are only few in the market because, this Carbohypaper Pineapple Leaf is made from waste product. So we do get advantages from doing this business because it is (less number of competitors. It also can give a long term profit to the company. Moreover, all our share partners of this business were actually had same interesting towards the product that we have been made. In administration management, we are concentrating on the organization reason of the company. We might want to guarantee that our business will run easily, proficiently and successfully with the goal that we can pick up benefits as much as we can. Organization division is additionally a sort of office who dependable to deal with the organization obligations of the organization, for example, making rules for the occupation obligations and occupation in charge of each worker, setting up the compensation calendar of the representatives, deal with alternate organizations of the company, for example, about the bills, utilities and so on. Generally, an orderly and decent arranging can guarantee the business or organization achievement. In the marketing department, we are entering in how to advance our items and services to other individuals whether to our present clients or to our potential clients. With a specific end goal to enhance our showcasing and to get the benefits, we additionally think About our shortcoming and qualities in the business. Moreover, we likewise make some observation and learn about our rival to decide our rival quality and shortcoming in the business. Advertising office is capable to examination the objective market and fitting advancement to expand our deals . At that point, this department will watch other organization promoting systems so as to tum out with the best method to advertise our items and administrations all through the nation. In the operation division, we concentrate on the most proficient method to utilize and to work the organization effectively and effectiveness. Operation division will deal with the operation procedure of the organization. The office will decide the suitable approach to be utilized as a part of request to deliver our item and services. The division additionally will decide the procedure that will be required during the production process. Operation office likewise will decide the suitable measure of any measure of any materials of crude materials or crude materials to be utilized as a part of request to create a specific item. Last but not least, the other department in the J-Pine Enterprise is the financial department. The financial department will be the division which mindful to deal with the budgetary matter of the organization. Financial office likewise capable to watch the stream of the cash, set up the last records and make any essential expectations about what the organization can do to increase and upgrade our benefits.